Commercialized innovative herbal products from UPM - Mohamed, Suhaila; Mohd Nor, Fatihanim (Institut Penyelidikan Perhutanan Malaysia, 2015)
The product invention is an additive which can be incorporated into edible oil composition especially cooking oil to provide therein antioxidant effect and reduce oil adsorption into the food prepared. The additive is composed of biophenolics formulated from plant extracts of the Rutaceae family. The antioxidant characteristics of Rutaceae leaf alcohol extract were evaluated in refined, bleached and deodorized (RBD) palm olein at 180oC using an accelerated oxidation and deep frying studies for up to 40 hours. The extract, at the optimum concentration 0.1%, retarded oil deterioration significantly (P<0.05) in deep frying studies, comparable to 0.02% BHT (Butylated Hydroxy Toluene) in tests such as peroxide value, anisidine value, free fatty acid, Oxidative Stability Index (OSI), polar and polymer compounds content. The sensory evaluation of french fries fried in oil containing the extract showed significant (P<0.05) improvement in crispiness, taste and overall quality, especially after the 40th hour of frying compared to those similarly fried in the control oils and the oils containing BHT. The polyphenols content of the extract were 103.2 mg/g gallic acid equivalent. Rutaceae leaf extract exhibited excellent heat stable natural antioxidant properties that retarded oil degradation and improved the quality of the fried product.